Chemically characterised Artemisia nilagirica (Clarke) Pamp. essential oil as a safe plant-based preservative and shelf-life enhancer of millets against fungal and aflatoxin contamination and lipid peroxidation. (3rd May 2020) - Kumar, Manoj; Dwivedy, Abhishek Kumar; Sarma, Parismita; Dkhar, M. S.; Kayang, H.; Raghuwanshi, Richa; Dubey, Nawal Kishore
Abstract: The study recommends the Artemisia nilagirica (Clarke) Pamp. essential oil (ANEO) as plant-based shelf-life enhancer of millets against fungal, aflatoxin B1 (AFB1 ) contamination and lipid peroxidation with favourable safety profile. Chemical characterisation of ANEO through GC-MS, recorded 1, 5-heptadiene-4-one, 3, 3, 6-trimethyl (32.72%)as the main compound, followed by Artemisia alcohol (13.40%), alpha lonone (4.55%), benzene, methyl (1-methylethyl) (2.97%) and 1-cyclohexene-1-carboxaldehyde, 4-(1-methylethyenyl) (2.23%). The mycoflora analysis of millet samples showed Aspergillus flavus strain[LHP(R)-5] as the most AFB1 secreting strain. The ANEO inhibited growth and AFB1 production by the toxigenic strain at 1.4 and 1.0 µL mL −1, respectively, and also possess broad fungitoxic spectrum. The decrement in membrane ergosterol content, enhanced leakage of cellular Ca 2+, K + and Mg 2+ ions along with SEM and TEM study of ANEO-treated cell denotes plasma membrane as antifungal site of action. The ANEO also showed strong antioxidant activity as determined by DPPH and ABTS + assays having IC50 value 2.51 and 1.07 µL mL −1, respectively. More than 70.78% protection of Ragi samples from fungal contamination was observed during in situ trial. The ANEO showed favourable safety profile with high LD50 value (7528.10 µL kg −1 ) for male mice and also exhibited non-phytotoxicity for Ragi seeds germination.